Operation of gas turbines (Gas turbine power generation)
The objective of this module is to present the factors involved in operation of the gas turbine generating unit, including typical procedures for start-up and shut-down of the unit. On-load operation is discussed with particular emphasis on operating hazards and limition. This module generally focuses on the heavy industrial type gas turbine. Topics include start-up and shutdown procedure, governor control, exhaust temperature control, operating hazards, mechanical, thermal and combustion.